China\'s financial statecraft and the internationalization of the Renminbi: what looms over Brazil\'s foreign exchange reserves? - Dominguez, Antonio Cesar (2019)
In the XXI century, the foreign affairs community has observed the resurgence of geoeconomics - the use of economic means to geopolitical purposes. This time around, however, emerging powers are at the centre stage and the instruments of choice are based upon monetary and financial capabilities, such as currency swap agreements, trade policies, credit lines, and foreign investment. This process has been defined as Financial Statecraft. The reasons for this phenomenon, albeit manifold, relate to the fact that traditional geopolitical tools (e.g. armed forces) are not as effective in today\'s geopolitics as they used to be - e.g. during the Cold War. In this context, due to its economic growth, massive foreign exchange reserves and high level of savings, China has acquired enough financial power to employ it globally, making it a top international creditor, a major foreign investment source, and issuer of an international reserve currency. These developments have been reflected in Brazil. China not only is the largest trading partner, but also one of the major sources of foreign capital to the Brazilian economy. Brazil lacks capital to meet its needs of investment, especially in infrastructure, whereas China needs steady flows of commodities and has abundant financial resources. Against this backdrop, these countries have developed a deep economic and financial partnership, which is illustrated by their prolific cooperation in the last decades, such as common stances regarding the reform of the international financial institutions and the establishment of the BRICS initiative. In this context, this article analyzes the Chinese Financial Statecraft in relation to Brazil and assesses a scenario in which China deploys financial statecraft instruments to coax the Brazilian state into including the yuan in its currency reserves. We find that, owing to Brazil\'s moderate-to-high level of stateness and low threats to its strategic interests in case of compliance, the Chinese attempt would likely be successful.